Comparison between tris-citric acid yolk, yolk albumin citrate and skimmed milk extenders on sperm motility, livability and mass movement in frozen-thawed goat sperm - Nor-Ashikin, M.N.K.; Abdullah, Ramli (2011)
This experiment was carried out with the aim to compare the effect of three extenders on frozen-thawed sperm characteristics in goat. Sperm of Katjang and their crossbreds; Jermasia and Jermana were cryopreserved in three extenders namely tris-citric acid yolk (TCAYE), yolk albumin citrate (YACE) and skimmed milk (SME) and the frozen-thawed sperm parameter were examined. The finding of this study showed that the Jermasia and Jermana buck sperm cryopreserved in TCAYE provided the best results in terms of motility (52.64 +/- 0.93% and 53.20 +/- 1.13%) and livability (56.47+/- 0.96% and 57.72 +/- 1.11%), respectively. In the crossbreds, sperm motility and livability in TCAYE were found to be significantly higher compared to the sperm cryopreserved in YACE and SME. Therefore, TCAYE extender apparently is better than YACE followed by SME for the cryopreservation of goat sperm.